2016
DOI: 10.3892/mmr.2016.5160
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126 inhibits tumor cell invasion and metastasis by downregulating ROCK1 in renal cell carcinoma

Abstract: MicroRNAs (miRNAs) are involved in cancer development and progression. Renal cell carcinoma (RCC) frequently undergoes metastasis and has a high mortality rate. The current study measured miRNA-126 (miR-126) expression levels in 128 pairs of clear cell RCC and adjacent normal kidney tissue samples by reverse transcription-quantitative polymerase chain reaction, and analyzed the association between miR-126 and various clinicopathological parameters. In addition, cell proliferation, wound healing and cell invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
(39 reference statements)
0
18
0
1
Order By: Relevance
“…MiR-126 is considered an endothelial cellrestricted miRNA that mediates inflammation and vascular development and has been reported as an important therapeutic treatment for various diseases involving aberrant inflammation and vascular leakage. 16 A report from our laboratory has demonstrated that the miR-126 pathway may contribute to ameliorating DR through its ability to enhance vascular repair and reduce inflammatory effects. 17 Previous research also showed that miR-126 plays a key role in modulating the expression of inflammatory factors after hyperglycemia-induced retinal inflammation.…”
mentioning
confidence: 99%
“…MiR-126 is considered an endothelial cellrestricted miRNA that mediates inflammation and vascular development and has been reported as an important therapeutic treatment for various diseases involving aberrant inflammation and vascular leakage. 16 A report from our laboratory has demonstrated that the miR-126 pathway may contribute to ameliorating DR through its ability to enhance vascular repair and reduce inflammatory effects. 17 Previous research also showed that miR-126 plays a key role in modulating the expression of inflammatory factors after hyperglycemia-induced retinal inflammation.…”
mentioning
confidence: 99%
“…Western blotting analysis was performed as described previously. 15 Briefly, cells were harvested using the CelLytic extraction kit supplemented with protease inhibitors. Protein concentration was measured using the BCA Protein Assay reagent kit (Thermo Fisher Scientific) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Jiang et al (2014) concluded that miR-126 inhibits cell growth, invasion and migration of osteosarcoma cells. Zhang et al (2016) concluded in their study an association of miR-126 with CRC progression and metastasis, thus suggesting that this microRNA may function as a tumor suppressor involved in the development of CRC, being a potential biomarker in the diagnosis and therapeutic act.…”
Section: Introductionmentioning
confidence: 99%